2022
DOI: 10.5530/pres.14.3.39
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Caffeine Consumption in Western Province of Saudi Arabia

Abstract: Introduction: Caffeine is the most consumed psychoactive drug worldwide. Nowadays, the introduction of many caffeine-containing products, along with changes in the consumption patterns of both natural and synthetic sources of caffeine, has drawn the attention of health researchers. Information regarding consumption patterns of coffee and caffeinated products among the Saudi population, particularly in different regions, remains unclear. Thus, this study aims to identify the amount and sources of caffeine consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…This was consistent with previous studies conducted in Saudi Arabia [ 13 , 21 , 26 ], which indicated that these students were aware of the side effects, including hypotension, fatigue, and shortness of breath. Although caffeine consumption improves performance and mental alertness, evidence indicates that the consumption of high levels of caffeine can be related to increased anxiety levels [ 29 ]. According to our results, the participants who drank coffee while studying and preparing for their exams had greater levels of anxiety and were likelier to use propranolol than students who did not consume coffee.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous studies conducted in Saudi Arabia [ 13 , 21 , 26 ], which indicated that these students were aware of the side effects, including hypotension, fatigue, and shortness of breath. Although caffeine consumption improves performance and mental alertness, evidence indicates that the consumption of high levels of caffeine can be related to increased anxiety levels [ 29 ]. According to our results, the participants who drank coffee while studying and preparing for their exams had greater levels of anxiety and were likelier to use propranolol than students who did not consume coffee.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers prepared the questionnaire following guidelines from past studies in the Arab region involving Arabic questionnaires [ 13 ]. Experts from the Faculty of Medicine and Pharmacy at Jazan University assessed the questionnaire and offered feedback and suggestions for improvement.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Another study in the Western Province of Saudi Arabia showed that females represented 80% of caffeine consumers. [3] Studies have shown that caffeine's effects on men and women may differ. Caffeine may have a greater impact on women's blood pressure and heart rates than on men.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Energy drinks are becoming increasingly popular in the country, with brands like Red Bull and Monster Energy having a solid presence in the Saudi Arabian market. [2,3] Caffeine is included in many over-the-counter pain medications, such as Panadol Extra and Fevadol Extra, since it acts as an aid, in some cases increasing the effect of pain relievers by 40%. It also works as a vasoconstricting and anti-inflammatory agent.…”
Section: Introductionmentioning
confidence: 99%